Analysis on Cattaneo-Christov heat flux in three-phase oscillatory flow of non-Newtonian fluid through porous zone bounded by hybrid nanofluids - J. Hasnain (Case Studies in Thermal Engineering, 2022)
The primary aspect of this study is a theoretical analysis of heat transfer enhancement in the unsteady three-phase oscillatory flow of Casson fluid bounded by the layers of nanofluid and hybrid nanofluids flowing adjacent to the walls of a long-infinite horizontal composite channel. Stoke’s model is employed to define Casson fluid, and one phase model is implemented for nanofluid. Moreover, Cattaneo–Christov heat flux model is also considered. This model amends Fourier’s law of heat transport using thermal relaxation time due to which heat passes through the channel within a finite limit. Analytical solutions are attained through a regular perturbation technique by employing periodic and non-periodic functions and presented through graphical illustrations by implementing the MATHEMATICA program. The outcomes are exhibited with three types of nanomaterials such as copper Cu, copper oxide CuO and copper alumina Cu–Al2O3 with base fluid as water. It is noted that the momentum and heat transport is significant in the case of Casson fluid with porous zone sandwiched between Cu water NFs as compared to Cu–CuO–H2O (phase I) and Cu–Al2O3–H2O (phase III) HNFs. Moreover, in the case of injection, it is observed that the effects of Cu nanomaterials are dominant on temperature. On the other side, in suction, the impacts of Cu–Al2O3 nanomaterials are significant on temperature. The results are also compared with a well-known numerical method named as finite element method.